SI-PANDA: Web-Based Personnel Data and Dossier Management System for Pusinfolahta TNI - Muhammad Sulthan Nasyira; Eryan Ahmad Firdaus (FKOM UNIKU, 2026)
Pusinfolahta TNI currently faces critical inefficiencies in personnel administration due to reliance on manual spreadsheet calculations and decentralized local storage for dossier documents. This manual workflow poses significant risks to data security, accuracy, and retrieval speed. To address these limitations, this research developed the Personnel Data and Dossier Processing System (SI-PANDA) utilizing the Rapid Application Development (RAD) method to ensure iterative improvements based on user feedback. The system is constructed upon a three-tier architecture comprising a Native PHP backend, MySQL database, and a responsive web interface. Testing results demonstrate significant performance improvements: the system achieves a page load time of 1.2 seconds and near-instant calculation speed (0.05 seconds) for tenure and retirement estimation, ensuring 100% calculation accuracy. Furthermore, Blackbox testing confirmed the validity of all functional requirements, including the automated backup mechanism and search filters. The main contribution of this study is the delivery of a secure, integrated digital framework that successfully transitions Pusinfolahta TNI from manual processing to a reliable web-based environment, specifically adapted to meet military administrative standards.